La satisfacción laboral y su efecto en la satisfacción del cliente, un análisis teórico - Guerrero Bejarano, Maria Auxiliadora (2018)
There are various studies that suggest that the satisfaction of the employee has a correlation with the satisfaction of the clients. On the service end there are various components from the comprehensive service management that if done in unison with a management committed to motivate the team; the results will be a company that achievesthe highest level of service.A very important factor is the personnel, it is important to consider the fact that for all its policies, manuals, procedures, work instructions, scripts and acting protocols that the company has implemented, if the staff is not highly motivated and with a positive attitude at the time they are fulfilling their assignment in the position they are in, they will portrait dissatisfaction towards their client.A satisfied employee transmits a positive attitude that translates to happy and satisfied clients that will contribute to the profitability of the organization (Christopher Lovelock, 2011).